P.063 SUNFISH Part 1 results and Part 2 trial design in patients with type 2/3 spinal muscular atrophy (SMA) receiving risdiplam (RG7916). (5th June 2019) - Campbell, C; Mercuri, E; Baranello, G; Kirschner, J; Servais, L; Goemans, N; Pera, M; Buchbjerg, J; Yeung, W; Kletzl, H; Gerber, M; Czech, C; et al.
Abstract : Background: SMA is characterized by reduced levels of survival of motor neuron (SMN) protein from deletions and/or mutations of the SMN1 gene. While SMN1 produces full-length SMN protein, a second gene, SMN2, produces low levels of functional SMN protein. Risdiplam (RG7916/RO7034067) is an investigational, orally administered, centrally and peripherally distributed small molecule that modulates pre-mRNA splicing of SMN2 to increase SMN protein levels.Methods: SUNFISH (NCT02908685) is an ongoing multicenter, double-blind, placebo-controlled, operationally seamless study (randomized 2:1, risdiplam:placebo) in patients aged 2–25 years, with Type 2/3 SMA. Part 1 (n=51) assesses safety, tolerability, pharmacokinetics and pharmacodynamics of different risdiplam dose levels. Pivotal Part 2 (n=180) assesses safety and efficacy of the risdiplam dose level selected based on Part 1 results.Results: Part 1 results showed a sustained, >2-fold increase in median SMN protein versus baseline following 1 year of treatment. Adverse events were mostly mild, resolved despite ongoing treatment and reflected underlying disease. No drug-related safety findings have led to withdrawal (data-cut 06/17/18). SUNFISH Part 1 exploratory endpoint results and Part 2 study design will also be presented.Conclusions: To date, no drug-related safety findings have led to withdrawal. Risdiplam led to sustained increases in SMN protein levels.